Health literacy of informal caregivers on Alzheimer's disease - Sarmento,Beatriz (2022)
Abstract Introduction: Considering population aging and the demographic projections for Portugal, is expected an increase in the development of chronic degenerative diseases, as is the case of Alzheimer's Disease (AD). Thus, Informal Caregivers (IC) have a fundamental role in the provision of care, which is influenced by the literacy level of such population. Objective: To explore the level of literacy of Informal Caregivers on Alzheimer's Disease. Methods: Descriptive, exploratory and quantitative study, with a sample of 28 participants. The data collection took place through a questionnaire and the Alzheimer's Disease Knowledge Scale, on Google Forms, after informed consent. Results: Most IC were female (75%), with an average of 54,04 years of age (12,46), a high level of educational qualifications and a close relationship with the person cared for. They provide care on average 4,18 years ((2,41), approximately 12 hours a day, seven days a week. Regarding the difficulties felt, the majority reported neurobehavioral changes in AD, management of personal and professional life, lack of support and uncertainties of personal training to care. It is considered that 57,14% of IC have an intermediate level (3 on a scale of 1-5) in the way they provide care. Conclusion: Due to the difficulties and needs mentioned by IC, the creation of new health literacy programs in the community is essential. In future studies it is important to evaluate the effectiveness of these programs in order to promote care strategies for IC of people with AD.